Integrin-dependent translocation of p160ROCK to cytoskeletal complex in thrombin-stimulated human platelets. - Fujita, A (1997)
p160(ROCK) is a protein serine/threonine kinase that binds to GTP-Rho and is activated by this binding. We have recently found that the expression of p160(ROCK) induces focal adhesions and stress fibres in HeLa cells, whereas a dominant-negative form of this kinase suppresses Rho-induced formation of these structures, suggesting that this kinase is a downstream target of Rho in this process [Ishizaki, Naito, Fujisawa, Maekawa, Watanabe, Saito and Narumiya (1997) FEBS Lett. 404, 118-124]. To find out the mode of action of p160(ROCK), we developed immunoblotting with an anti-p160(ROCK) antibody and investigated the subcellular localization of p160(ROCK) during platelet aggregation. In resting human platelets, more than 90% of p160(ROCK) was present in the Triton X-100-soluble fraction. When platelets were stimulated with thrombin, approx. 10% of p160(ROCK) was translocated to the Triton X-100-insoluble fraction. This translocation was detected as early as 20 s after stimulation and reached a maximum at 5 min; it was suppressed by the addition of EDTA or an Arg-Gly-Asp-Ser peptide (RGDS), both of which inhibit integrin alphaIIbbeta3-mediated platelet aggregation. Using [32P]Pi-loaded platelets, we found that p160(ROCK) was phosphorylated in response to stimulation by thrombin. This phosphorylation, however, was not affected by the addition of EDTA and RGDS. These results suggest that p160(ROCK) translocates to cytoskeleton in a manner dependent on integrin ligation and works in an early stage of cytoskeletal reorganization in thrombin-stimulated platelets.